Red metropolitana para la gestión de sucursales de la empresa SERVILOZA S.A - Roca Chucad, Marcos Antonio (2017)
In today's world is subject to many changes, such as telecommunications networks and others, this allows us to observe how technology has evolved very quickly helping us in the performance of our lives. In the company SERVILOZA S.A of the county of Ventanas Province of the Rivers, the sales have increased daily and which have managed to increase a branch to a few blocks of the main place. In the branch of the company mentioned above through an observation to the network it was possible to obtain that it has a network in bad condition which does not allow them to communicate with the main premises and at the same time the owner of the company does not allow him to carry an administration total of its businesses from the main premises, since the network equipment of this company are in poor condition, misconfigured and some equipment that are not acts for this type of work.